Efektivitas Proyek Penguatan Profil Pelajar Pancasila dalam Membangun Karakter Siswa - Septika, Nurleni (Journal of Innovation in Teaching and Instructional Media, 2024)
This study aims to examine the Effectiveness of the Pancasila Student Profile Strengthening Project (P5) in building student character at SD Negeri 149 Palembang. The main focus of the research is to understand how values such as mutual cooperation, independence, noble character, and global diversity are internalised by students through the implementation of P5 as well as to evaluate the challenges and successes in the implementation of the project. This research uses a descriptive qualitative approach with data collection techniques in the form of Diagnostic Assessments, observations, and in-depth interviews with teachers and students related to P5 activities. The results of the study show that P5 at SD Negeri 149 Palembang has been very effective in building students' character. The value of mutual cooperation and independence showed a high level of internalization, with more than 80% and 85% of students showing good cooperative behavior initiative in independent learning and cooperation. However, the value of global diversity and noble character still requires further efforts to be internalized more deeply, even though there has been progress in 60-65% of students while the value of creative and critical reasoning is at 70%. This study adds empirical insights into how the implementation of P5 in elementary schools concretely contributes to the development of students' character related to the effectiveness of the Project-Based Learning method in the context of character education in Indonesia.